Kausalitas dalam Perspektif Teologi dan Filsafat Al-Ghazali - Firdiansyah, Adin Lazuardi; Alfiyatin, Yuliana (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
Al-Ghazali is often cited as the first theologian to systematically explain the inevitability of cause-and-effect relationships. In fact, Al-Ghazali did not reject the law of causality, but what he rejected was the view of Muslim philosophers who said that causality is a necessity or certainty. This literature research aims to analyze Al-Ghazali's thoughts about causality from two points of view at once: theology and philosophy. The author finds that in al-Ghazali's view, causality is only an appearance and is the impact of the human habit of linking two events that occur consistently in nature. Religion according to Al-Ghazâlî must be defended from attacks by philosophy. The dynamics of these beliefs and attitudes are closely related to critical responses to the thoughts of Muslim philosophers. Therefore, socio-historically, Al-Ghazâlî's argument about causal relationships cannot be used as a holistic benchmark or standard that this is Al-Ghazâlî's true view and attitude